2004
DOI: 10.22358/jafs/67631/2004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substitution of dietary protein with carbohydrate on lactation performance in the mink (<i>Mustela vison</i>)

Abstract: Thirty mink dams nursing litters of 6 kits were assigned to one of 3 dietary treatments to investigate the effects of changing the protein:carbohydrate ratio on nutrient utilization, heat production, milk production and kit growth. Three diets were formulated to contain 65:3 (LC), 48:15 (MC) or 34:33 (HC) % of the metabolizable energy (ME) from protein and carbohydrate, respectively. The diets were fed ad libitum for 4 weeks from parturition. Twelve dams were held in an intensive care unit and subjected to bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…This approach is described for mink to separate total HE of lactating mink dams and suckling kits measured by indirect calorimetry (Fink, 2004). Raising the liveweight of individual piglets to the power of 0.75 and taking the sum gave the metabolic liveweight of the litter.…”
Section: Methodsmentioning
confidence: 99%
“…This approach is described for mink to separate total HE of lactating mink dams and suckling kits measured by indirect calorimetry (Fink, 2004). Raising the liveweight of individual piglets to the power of 0.75 and taking the sum gave the metabolic liveweight of the litter.…”
Section: Methodsmentioning
confidence: 99%
“…Further, Russell et al (2002) found that protein oxidation was correlated to some extent to dietary protein intake in cats, but only if the protein requirement was met (Green et al, 2008). Studies in mink have, however, shown that the rates of amino acid decarboxylation (Tauson et al, 2001) and protein oxidation are regulated according to the dietary protein supply, even if the level of dietary protein is low (Fink et al, 2004) or below the requirement (Matthiesen et al, 2010a). These findings indicate some metabolic flexibility in the strict carnivores.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, mink dams fed a diet containing 30% of ME from protein have been shown to have a superior milk yield and be raising kits that gained more weight Archives of Animal Nutrition 247 during their first four weeks of life than kits raised by dams given diets containing high (60% of ME) and medium (45% of ME) protein supply (Fink et al 2004(Fink et al , 2006. These studies did, however, not go beyond a kit age of four weeks and therefore the impact of protein supply on kit body gain and performance in the transition period from milk to solid feed was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the knowledge on the protein and amino acid requirements for late gestation and lactation in e.g. Lactating mink dams though may actually benefit from diets with lower than conventional protein content: when the dietary protein supply was reduced to 30% of metabolisable energy (ME) and replaced with readily digestible carbohydrates, milk yield of the dams was improved and this was consequently reflected in improved kit growth during the first four weeks of lactation (Fink et al 2004(Fink et al , 2006. For cats, NRC (2006) states that the requirement has not been investigated in detail, but that it is not likely to be higher than in young growing kittens for which solid recommendations exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation